Gel properties of chicken-squilla low-fat mince gel with inulin: Physicochemical properties, microstructure, intermolecular interactions, and formation mechanism - Lijing Geng; Jing Liang; Dan Wang; Wei Huang; Hang Fu; Mbinga Isequias Elamba Tertulliano; Muhammad Zain Ul Aabideen; Wei Zhou; Quimbamba Silvia Jacinta Calombe; Aqsa Shafique (Food Chemistry: X)
This study aimed to examine the relationship of inulin with the chicken-Squilla mince mixture gel (CSMMG). The gel characteristics, microstructure, and intermolecular interactions, and formation mechanism of CSMMG with different inulin were determined. The cooking yield, water-holding property, color value, hardness, elasticity, chewiness, sensory score, microstructural denseness of CSMMG increased as the inulin, maximum at 5 %. Additionally, inulin could promote the formation and hydrophobic interaction of sulfhydryl group, hydrogen bond, disulfide bond, α-helix, and reduce the carbonyl content. According to PCA, PC1 had a positive correlation with chewiness, springiness, hardness, hydrophobic interactions, and negative with redness. Inulin obviously enhanced the gelling behavior of myofibrillar protein molecules with a denser and more uniform network structure by the hydrogen bonding between the myosin and inulin. This study will offer a theoretical basis for future research and development of low-fat high-protein meat products.